Study of Forced Convection Heat Transfer of Supercritical CO2 in a Horizontal Channel by Lattice Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2021)
The problem of forced convection heat transfer of supercritical CO2 in ahorizontal channel is investigated numerically by a lattice Boltzmann method. Thisstudy is stimulated by our recent experimental findings on solar collectors using supercriticalCO2 as a working fluid, which can achieve the collector efficiency highup to 70%. To deeply understand the heat transfer characteristics of supercriticalCO2 and provide a theoretical guidance for improving our current experimentalsystem, in present study several typical experimental flow conditions are simulated.In particular, the work focuses on the convective heat transfer characteristicsof supercritical CO2 flowing in a horizontal channel with mediate Reynolds numbersranging from 210 to 840 and constant heat fluxes from 400.0 to 800.0 W/m$^2$.The simulations show that the heat transfer increases with heat flux and decreaseswith Reynolds number. Furthermore, the mechanisms of heat transfer enhancementof supercritical CO2 fluid are identified.